2014
DOI: 10.1371/journal.pone.0090599
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Molecular Diagnosis of Bardet-Biedl Syndrome by High-Throughput Targeted Exome Sequencing

Abstract: Bardet-Biedl syndrome (BBS) is an autosomal recessive disorder with significant genetic heterogeneity. BBS is linked to mutations in 17 genes, which contain more than 200 coding exons. Currently, BBS is diagnosed by direct DNA sequencing for mutations in these genes, which because of the large genomic screening region is both time-consuming and expensive. In order to develop a practical method for the clinic diagnosis of BBS, we have developed a high-throughput targeted exome sequencing (TES) for genetic diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…Of note, among the total 124 mutation described in this study, 79 mutations were previously reported worldwide. We previously screened five patients with Bardet-Biedl syndrome for BBS genes 10 and five patients with Usher syndrome for USH genes 7 using the same panel; these were considered pilot studies to test the methodology and have been excluded from this study. Summarizing all these results, the detection rate was 57.7% (109/189).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, among the total 124 mutation described in this study, 79 mutations were previously reported worldwide. We previously screened five patients with Bardet-Biedl syndrome for BBS genes 10 and five patients with Usher syndrome for USH genes 7 using the same panel; these were considered pilot studies to test the methodology and have been excluded from this study. Summarizing all these results, the detection rate was 57.7% (109/189).…”
Section: Discussionmentioning
confidence: 99%
“…9 In pilot studies, we successfully performed molecular diagnoses in patients with Usher syndrome and Bardet-Biedl syndrome by assessing a panel of 144 known genes. 7,10 Despite success in previous studies, there is still a large proportion of patients with IRD who have unidentified genetic mutations. 2 In addition, there are few thorough studies of the relationship between specific genotypes and phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, only a few instances of BBS have been reported in Eastern Europe, Asia, South America, and Africa, and systematic BBS studies still remain to be done in these regions Xing et al, 2014;Ece Solmaz et al, 2015;Hirano et al, 2015;Suspitsin et al, 2015]. There are (1) the Clinical Registry Investigating Bardet-Biedl Syndrome (CRIBBS) at the Marshfield Clinic (https://www.marshfieldclinic.org/services/bardet-biedl-syndrome-(bbs); https://cribbs.marshfieldclinic.org/), (2) the Europeanbased EURO-WABB registry [Farmer et al, 2013], and a number of robust international studies Ajmal et al, 2013;Fattahi et al, 2014] attempting to attract unstudied patients to BBS research.…”
mentioning
confidence: 99%
“…Next, the release of IFT27 allows the activation of BBS3/ARL6 by GTP binding and attachment of (20) Joubert Syndrome 8 612291 ARL13B Yes (21) Meckel Syndrome 9 614209 B9D1 No (22) Bardet-Biedl Syndrome 1 209900 BBS1 Yes (15,(23)(24)(25) Bardet-Biedl Syndrome 2 615981 BBS2 Yes (23,25,26) Bardet-Biedl Syndrome 3 600151 BBS3/ARL6 Yes (27) Bardet-Biedl Syndrome 4 600374 BBS4 Yes (23,25,28) Bardet-Biedl Syndrome 5 615983 BBS5 Yes (23,29) Bardet-Biedl Syndrome 6 605231 BBS6/MKKS Yes (25,30) Bardet-Biedl Syndrome 7 615984 BBS7 Yes (23) Bardet-Biedl Syndrome 8 608132 BBS8/TTC8 Yes (23)(24)(25) Bardet-Biedl Syndrome 9 615986 BBS9/PTHB1 Yes (31) Bardet-Biedl Syndrome 10 615987 BBS10 Yes (15,23,25,32) Bardet-Biedl Syndrome 11 615988 BBS11/TRIM32 No (33) Limb-girdle muscular dystrophy 2H 254110 Id. No (34) Bardet-Biedl Syndrome 12 615989 BBS12 Yes (23) Bardet-Biedl Syndrome 13 615990 BBS13/MKS1 Yes (15,35) Meckel Syndrome 1 249000 Id. No (36) Bardet-Biedl Syndrome 14 615991 BBS14/CEP290/NPHP6 Yes (15) Leber congenital amaurosis 611755 Id.…”
Section: Intraflagellar Transportmentioning
confidence: 99%